2015
DOI: 10.12973/iji.2015.819a
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive Strategy Instruction as a Means to Improve Listening Self-Efficacy among Iranian Undergraduate Learners of English

Abstract: Metacognitive strategy instruction (MetSI) has been shown to have a strong impact on various aspects of English as a second/foreign language instruction. The present study aimed to investigate the effect of MetSI on the improvement of listening selfefficacy among English-as-a-foreign-language (EFL) learners. A group of sixty female undergraduate learners of English literature at a state-run university in Iran consented to take part in this study. After homogenizing the participants' English proficiency level u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 38 publications
0
18
1
Order By: Relevance
“…In general, their research results showed that the use of metacognitive strategies in learning could enhance students' thinking ability. Rahimirad and Zare-ee (2015) also reported that metacognitive strategies in learning could improve students' self-efficacy.…”
Section: Introductionmentioning
confidence: 95%
“…In general, their research results showed that the use of metacognitive strategies in learning could enhance students' thinking ability. Rahimirad and Zare-ee (2015) also reported that metacognitive strategies in learning could improve students' self-efficacy.…”
Section: Introductionmentioning
confidence: 95%
“…In the EFL/ESL context, several studies focused on the research regarding self-efficacy beliefs in all the four skills of English language. For instance, several studies are on listening self-efficacy (i.e., Rahimirad & Zare-ee, 2015;Taguchi, 2018;Todaka, 2017), on speaking self-efficacy (i.e., Idrus & Salleh, 2017;Kamaruddin & Zawawi, 2017), on reading self-efficacy (i.e., Aro et al, 2018;McLean & Poulshock, 2018), and on writing self-efficacy (i.e., Ekholm, Zumbrunn, & Bandura (1997) defines self-efficacy beliefs as persons' perceptions regarding his capabilities to carry out particular actions. Self-efficacy beliefs denote persons' subjective anticipations of and devotion to achieve the academic tasks at hand (Lau & Roeser, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It very well may be concluded from this finding on the use of learning methodologies that the utilization of learning systems by learners right now admirable as the degree of use for every one of the techniques is moderate. This furthermore suggests there is still opportunity to get better on the usage of these systems to improve better perception of another language as analysts right now (Karami & Bagheri, 2014;Rahimirad & Zare-ee, 2015) have revealed that these learning strategies have a crucial positive result on the learning of another language.…”
Section: Resultsmentioning
confidence: 99%